The Impact of COVID-19 Pandemic on Distress Intolerance: Among Panic Buyers in Turkey - Öncel, Sevgi Yurt; Erdugan, Funda (International Journal of Statistics in Medical Research, 2023)
In this study, the factors affecting levels of distress intolerance during the Covid-19 pandemic are statistically analyzed among panic buyers in Turkey. Distress intolerance also increased as health status deteriorates. Construct consistency was achieved in measuring distress intolerance during the Covid-19 period. Confirmatory factor analysis (CFA) was performed for participants who engage in panic buying behavior. CFA showed that the reliability and consisteny of this scale was ensured. It was seen that enduring uncomfortable emotions was the condition that affected distress intolerance the most. Doing everything to avoid feeling distressed or sad was found to be the least affecting distress intolerance in the Covid-19 period. When all of the fit criteria were considered, it was evident that the proposed model was valid for sample. Consequently, it is recommended that public health services develop health strategies with respect to the stated risk factors and to provide interventions that increase psychological flexibility to reduce Covid-19 related intolerance to distress.